Influence of alkyl chain length of alpha olefin sulfonates on surface and interfacial properties. Issue 12 (2nd December 2017) - Wang, Yong; Liu, Xiaochen; Bai, Long; Niu, Jinping
ABSTRACT: Alpha olefin sulfonates (AOS) with various alkyl chain lengths have been used to investigate the influence of alkyl chain length on the interfacial properties at air–water, liquid paraffin–water, and parafilm–water interfaces. It was found that the critical micelle concentration decreased with increasing alkyl chain length, while the efficiency of reducing surface tension was inverse relationship with alkyl chain length. The diffusion coefficient obviously reduced with an increase of surfactant concentration and alkyl chain length. The C14-16 AOS shows better wettability and emulsification than C16-18 AOS and C20-24 AOS. For foaming properties, the foamability and foam stability dramatically decreased with increasing alkyl chain length. GRAPHICAL ABSTRACT: